2020
DOI: 10.1371/journal.pone.0234702
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccination in older people: A systematic review and meta-analysis of the determining factors

Abstract: Background/Objectives Despite influenza vaccination programs in various jurisdictions, seasonal influenza vaccine (SIV) uptake remains suboptimal among older people (�65years old), an important subpopulation for influenza vaccination. We sought to summarize determinants of SIV uptake (any vaccine receipt) and vaccination adherence (receipt of vaccine in two or more seasons in sequence) among older people. Methods We searched for population-based studies conducted in community-dwelling older people (irrespectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 82 publications
(183 reference statements)
3
45
1
6
Order By: Relevance
“…Secondly, if a study reported results for more than one comparison of the same determinant, for example, the 25-29, 30-34 and 35-39 years age groups compared with the 18-24 years age group, results from the three comparisons were first pooled using a fixed-effects model before being pooled with other results for comparison of older against younger age groups, using a random-effects model. 24,25 We assessed and quantified statistical heterogeneity between the included studies using the I-squared statistic (I 2 ). 38 Where appropriate, publication bias was assessed visually using funnel plots, and statistically using Egger's regression test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, if a study reported results for more than one comparison of the same determinant, for example, the 25-29, 30-34 and 35-39 years age groups compared with the 18-24 years age group, results from the three comparisons were first pooled using a fixed-effects model before being pooled with other results for comparison of older against younger age groups, using a random-effects model. 24,25 We assessed and quantified statistical heterogeneity between the included studies using the I-squared statistic (I 2 ). 38 Where appropriate, publication bias was assessed visually using funnel plots, and statistically using Egger's regression test.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive search strategy was designed for Ovid MEDLINE by a health sciences librarian (CJN), based in part on the search strategy used in our previous similar publications (on older adults, PROSPERO registration: CRD42018086803) 24,25 . The search results were limited to publications in English since 2000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons behind the decision to receive vaccinations varied. Studies investigating factors associated with uptake of vaccinations, such as influenza vaccinations, have demonstrated that vaccination uptake was influenced by a range of personal and interpersonal factors [ 7 , 8 ]. Current studies on factors related to willingness to vaccinate against COVID-19 have also identified a number of demographics, cognitive and psychosocial factors of intention to receive the COVID-19 vaccination, including age, gender, education, having insurance, attitudes toward the vaccine, confidence in government information, perceived susceptibility to COVID-19, and perceived benefits and side effects of the vaccine [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some older adults may also be fearful of adverse effects, real or perceived, associated with the influenza vaccine [ 35 ]. Population reviews found that patients who are part of a visible minority group have lower household income, poor physical activity, lack of access to healthcare resources, and better overall health were more likely to not receive an influenza vaccine [ 36 , 37 , 38 ]. There is observational data demonstrating that having severe functional limitations (severe frailty) increases the risk of death by 13-fold but decreases the likelihood of influenza immunization [ 39 ].…”
Section: Discussionmentioning
confidence: 99%